2007
DOI: 10.1038/nrc2254
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in cancer

Abstract: Autophagy is a cellular degradation pathway for the clearance of damaged or superfluous proteins and organelles. The recycling of these intracellular constituents also serves as an alternative energy source during periods of metabolic stress to maintain homeostasis and viability. In tumour cells with defects in apoptosis, autophagy allows prolonged survival. Paradoxically, autophagy defects are associated with increased tumorigenesis, but the mechanism behind this has not been determined. Recent evidence sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
1,463
1
21

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,672 publications
(1,507 citation statements)
references
References 83 publications
22
1,463
1
21
Order By: Relevance
“…Autophagy has been associated with various aspects of innate and adaptive immunity, including interferon and cytokine production (Virgin and Levine, 2009). Moreover, autophagy can be subrogated by cancer cells to avoid the adverse micro-environmental stress (Mathew et al, 2007). Recent data has revealed that sustained activation of ERK and p38 plays critical roles in autophagy at the maturation step (Corcelle et al, 2006).…”
Section: Perspectivesmentioning
confidence: 99%
“…Autophagy has been associated with various aspects of innate and adaptive immunity, including interferon and cytokine production (Virgin and Levine, 2009). Moreover, autophagy can be subrogated by cancer cells to avoid the adverse micro-environmental stress (Mathew et al, 2007). Recent data has revealed that sustained activation of ERK and p38 plays critical roles in autophagy at the maturation step (Corcelle et al, 2006).…”
Section: Perspectivesmentioning
confidence: 99%
“…Secondly an antibody against caspase 3 (which is common to both the extrinsic and intrinsic apoptotic pathways),38 was used to identify cells which may be apoptotic. The third endpoint assessed was autophagy, a self‐digestion process that cells in stressed conditions undergo as part of their normal life cycle,39 but which has been linked to apoptosis 40. Although autophagy has also been implicated in cell survival, an apoptosis‐inducing drug has been previously shown to increase autophagosome numbers in osteosarcoma cells,41 whilst p53 has been shown to activate autophagy so as to increase the efficiency of apoptosis 42.…”
mentioning
confidence: 99%
“…Autophagy, or programmed cell survival, shares several common stimuli and signaling pathways with those of apoptosis (Maiuri et al, 2007). Autophagy is a tumorsuppression mechanism, yet it enables tumor-cell survival in settings of enhanced stress (Kondo et al, 2005;Mathew et al, 2007;White and DiPaola, 2009). Moreover, autophagy can degrade active caspase-8 within tumor cells (Hou et al, 2010).…”
mentioning
confidence: 99%